Charles Millard, A Canadian in the International Labour Movement: A Case Study of the ICFTU 1955-61 - Carew, Anthony (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
Shortly after its formation in 1949, the Interntional Confederation of Free Trade Unions (ICFTU) became hamstrung dy disagreements over cold war issues. General Secretary Oldenbroek's caution was criticized by the Americans, and Charles Millard, Candian Director of the Steelworkers, was appointed Regional Director, a post established to counterbalance Oldenbroek's influence and to revitalise the organization. However, Millard's zeal was insufficient to compensate for his shortage of interntional experience, and lack of guile left him vulnerable to opponents among the movement's power brokers. At odds with both the American and British union leaderships, he resigned in 1961, a victim of the constraints placed on labour internationalism by the Cold War.